Exploring the awareness, use and challenges facing the integration of artificial intelligence in library services by librarians in university libraries in North-Central, Nigeria - Odigie , Imoisili O. (Communicate: Journal of Library and Information Science, 2024)
This research delves into the integration of artificial intelligence (AI) in Nigerian university libraries, exploring the awareness, adoption, and potential impact of AI on library services. The study employs a qualitative approach, utilizing a case study design to capture the perspectives of reference librarians in the north-central geopolitical zone of Nigeria. Data were collected through semi-structured interviews with 52 reference librarians, focusing on their awareness of AI, motivators and mitigators to its use in library services, and concerns regarding its potential impact. Findings reveal that while reference librarians demonstrate a substantial awareness of AI tools such as ChatGPT and Gemini, their utilisation remains primarily for personal use rather than professional service delivery within libraries. Challenges such as training, and infrastructure mitigated the integration of AI into library operations, restricting its effectiveness in supporting students and faculty. This research underscores the need for targeted training programs and infrastructure investments to facilitate the effective adoption of AI in Nigerian university libraries. By understanding librarians’ perspectives and addressing their concerns, libraries can harness the transformative potential of AI to enhance service delivery and meet the evolving needs of their clientele in the digital era.